AMA handbook of business writing the ultimate guide to style, grammar, punctuation, usage, construction, and formatting - Wilson, K. (Kevin) 1958-; Wauson, Jennifer (American Management Association, 2010)
This handbook is a complete A to Z reference on everything you need to produce top-quality documents. You'll find more than 600 pages of instantly accessible, thoroughly useful information for getting any job done.